Penerapan Lean Management di Rumah Sakit dalam Meningkatkan Efisiensi dan Kualitas Layanan : Literature Review - Diana Safitri; Revina Rahmadani; Budi Hartono (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Lean Management is a method that emphasizes reducing waste and increasing added value in healthcare service processes. Through a systematic literature review, this study identifies various aspects of Lean implementation in hospitals, such as reducing patient waiting times, optimizing resource utilization, and improving patient satisfaction. The findings reveal that Lean Management implementation not only supports operational efficiency but also enhances service quality and patient experience. The success of this method heavily depends on management support, active staff involvement, and adequate training. This study also highlights challenges such as resistance to change and budget constraints. These findings have significant implications for hospital managers and policymakers in formulating strategies to improve healthcare service effectiveness. Recommendations for future research include empirical studies examining Lean implementation in various hospital contexts, particularly in developing countries. This study aims to explore and analyze strategies for improving hospital operational efficiency through the Lean Management approach.